Continuous Color‐Tunable Light‐Emitting Devices Based on Compositionally Graded Monolayer Transition Metal Dichalcogenide Alloys. Issue 44 (6th October 2022) - Pu, Jiang; Ou, Hao; Yamada, Tomoyuki; Wada, Naoki; Naito, Hibiki; Ogura, Hiroto; Endo, Takahiko; Liu, Zheng; Irisawa, Toshifumi; Yanagi, Kazuhiro; Nakanishi, Yusuke; Gao, Yanlin; et al.
Abstract: The diverse series of transition metal dichalcogenide (TMDC) materials has been employed in various optoelectronic applications, such as photodetectors, light‐emitting diodes, and lasers. Typically, the detection or emission range of optoelectronic devices is unique to the bandgap of the active material. Therefore, to improve the capability of these devices, extensive efforts have been devoted to tune the bandgap, such as gating, strain, and dielectric engineering. However, the controllability of these methods is severely limited (typically ≈0.1 eV). In contrast, alloying TMDCs is an effective approach that yields a composition‐dependent bandgap and enables light emissions over a wide range. In this study, a color‐tunable light‐emitting device using compositionally graded TMDC alloys is fabricated. The monolayer WS2 /WSe2 alloy grown by chemical vapor deposition shows a spatial gradient in the light‐emission energy, which varies from 2.1 to 1.7 eV. This alloy is incorporated in an electrolyte‐based light‐emitting device structure that can tune the recombination zone laterally. Thus, a continuous and reversible color‐tunable light‐emitting device is successfully fabricated by controlling the light‐emitting positions. The results provide a new approach for exploring monolayer semiconductor‐based broadband optical applications. Abstract : A color‐tunable light‐emitting diode is realized using compositionally graded monolayer transition metal dichalcogenide alloys. By controlling the light‐emitting positions in the alloys, the composition gradient of the bandgap enables continuous and reversible light emission with energies ranging from 2.1 to 1.7 eV. The results provide a new approach for exploring monolayer‐semiconductor‐alloy‐based broadband optoelectronic device applications.